PENINGKATAN PENGETAHUAN KADER STUNTING DI WILAYAH BINAAN PUSKESMAS BRINGIN MELALUI EDUKASI BERBASIS DIGITAL DENGAN METODE BRAINSTORMING DI ERA GLOBALISASI DALAM PENCEGAHAN STUNTING - Devi Pramita Sari Devi; Nur Hikmah; Fifi Anisa Nur Hidayati; Alifah Sari Nugraini (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Stunting is a condition of failure to grow to achieve normal growth due to poor nutritional status in a long period of time. In the preliminary study, there were 5 children under two who were stunted at the Bringin Health Center and it was found that there was a lack of training and knowledge of cadres related to stunting. PkM participants are Stunting Cadres assisted by Bringin Community Health Center. The purpose of this PkM activity is to increase the knowledge of stunting cadres through digital-based education with the brainstorming method in stunting prevention. This is the basis for conducting community service with the title "Increasing Knowledge of Stunting Cadres in the Assisted Areas of Bringin Health Center through Digital-Based Education With Brainstorming Methods in the Era of Globalization in Stunting Prevention". The activity stage was preceded by coordination and communication activities with the Head of the Puskesmas and the Head of Cadres of the Assisted Areas of the Bringin Public Health Center, Semarang Regency. The implementation of Community Service (PKM) is carried out offline through digital-based education using the brainstorming method. The outputs of this PkM activity are the publication of scientific articles in the PkM journal, a 5-minute video of PkM activities, and the integration of the results of PkM activities in courses. The output of this PkM is expected to have an impact on increasing knowledge, improving the quality of abilities, as well as the real practice of stunting cadres in the Bringin Community Health Center target area in stunting prevention.